Political control in Colombia (2013)
This article analyses the political control enshrined in the Constitution that initially remained in the hands of the Congress, exercised exactly for each of the cameras on the national Government. But that control was not only given to the legislator, but was also established to be enforced by means of departmental assemblies and municipal councils on governors and mayors, on occasion of their functions.